Senescence of Pear Fruit Cells Cultured in a Continuously Renewed, Auxin-deprived Medium - Pech, Jean-Claude (1979)
Auxins and cytokinins support cell division in tissue and cell cultures. In cytokinin-independent pear (Pyrus communis) cells, omission of 2,4-dichlorophenoxyacetic acid (2,4-D) from the medium for two successive transfers leads to rapid cell lysis, unless the osmolarity is raised to 0.4 molar with mannitol. Use of this system (nutrients plus mannitol minus 2,4-D) for the study of cell senescence was explored both in batch culture and in a system designed to permit medium renewal without withdrawal of live cells. In both systems, an initial period (1-6 days) of limited increase in cell number is characterized by a continuous decrease in the respiratory activity and in protein and RNA synthesis to very low basal rates. In batch culture, cell death occurs after 13 to 15 days with little or no change in metabolic activity, or in protein and RNA synthesis. With renewal of cell medium, death is slightly delayed and is preceded by a burst in RNA synthesis followed by a notable increase in protein synthesis. Cycloheximide inhibition of protein synthesis is transient and its effect on cell longevity variable. Nonetheless, in all instances cell death is preceded by a burst in protein synthesis. Actinomycin D (1.6 micromolar) did not significantly affect protein synthesis but delayed RNA synthesis and cell death. The possible roles of auxin, osmoticum, and macromolecular synthesis in cellular senescence and death are discussed.